(untitled) (Innovative professional education, 2024)
The roles of pedagogical workers in professional education in the conditions of mixed education during the war are outlined. The relevance of the ability to use ICT for the organization of the educational process in each specific educational discipline has been established. The importance of being able to organize pedagogical processes online is emphasized in such a way that students of education are involved as much as possible, are active participants and not observers, and so that, despite the circumstances of wartime, students feel the presence of a teacher in the role of a benevolent mentor. Emphasis is placed on the fact that during the training of professional education teachers in educational institutions or in advanced training courses, in addition to listening and learning the theoretical material, it is necessary to complete the entire part of the distance course on the educational discipline in stages. A recommended logical structure for the training of teachers of professional education for the implementation of blended learning has been developed.